Low risk of adenocarcinoma and high‐grade dysplasia in patients with non‐dysplastic Barrett's esophagus: Results from a cohort from a country with low esophageal adenocarcinoma incidence. Issue 3 (1st June 2016) - Pereira, António Dias; Chaves, Paula
Abstract : Background: The risk of esophageal adenocarcinoma (EAC) in non‐dysplastic Barrett's esophagus (NDBE) is considered to be approximately 0.3% per year or even lower, according to population‐based studies. Data from countries with low EAC incidence are scarce. Our principal aim was to determine the incidence of high‐grade dysplasia (HGD) and EAC in NDBE. Our secondary aims were to identify the predictors of progression and to calculate the incidence of HGD/EAC, by using the calculation method for surveillance time in population‐based studies. Materials and methods: A cohort of NDBE patients was prospectively followed up. Cases of HGD and EAC (study end points) diagnosed during the first year of follow‐up were considered as prevalent. Only cases with an endoscopic surveillance time > 1 year were included in our analysis. Results: We enrolled 331 patients (251 men) in the surveillance program. Their median age was 59 years (interquartile range (IQR): 47–67 years). Their median NDBE length was 3 cm (IQR: 2–4 cm). Of these patients, 80 died during the follow‐up (one from EAC) and two were lost to follow‐up. After 2284 patient‐years of endoscopic follow‐up (median surveillance time, 5 years (IQR: 2–10 years)), we found that five cases of HGD and two cases of EAC were diagnosed. The incidence of HGD/EAC was 3.1 cases per 1000 patient‐years (95% CI: 1.3–6.0) and that of EAC was 0.9 (95% CI: 0.2–2.9). The incidence of HGD/EAC in short segments (≤ 3 cm) was 0.7 cases per 1000 patient‐years (95% CI: 0.3–3.4). The sole variable that we found associated with progression was NDBE length. If the total surveillance time was considered (3537 patient‐years), the incidence of HGD and EAC was only slight lower. Conclusions: The incidence of HGD and EAC was very low in NDBE. Therefore, current surveillance guidelines must be reassessed, at least for short‐segment BE.